GLOBALIZATION AND FARMER SUICIDES IN INDIA - Dr. Haresh T. Gajbhiye , Dr. Narendra K. Patil, Prof. Manohar R. Chaudhari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Economic Impact While the economic aspect of globalization is not known, it can be said that a large part of the ongoing debate about globalization and the direction of this debate is related to this aspect. One aspect of this problem is how to define economic globalization. As economic globalization is mentioned, our focus is on international institutions like the International Monetary Fund and the World Trade Organization and the role played by them in determining economic policies around the world. However, globalization should not be viewed from such a narrow perspective. Apart from these international institutions, many players are also involved in economic globalization. To understand economic globalization from a more comprehensive view, we should think in terms of sharing the economic benefits from it, in terms of who benefited most from globalization and who did the least. It also needs to see who has suffered due to globalization. Due to liberalization and globalization, the import of food grains has already started at cheaper prices and on the other hand, farmers in our country are forced to burn their finished crops in the fields. The reason they are doing this is that they are not able to get a good price for their crops and sometimes the overall value they get after selling their crop is compared to the total amount they invested in farming Decreases a lot. The amount of loan taken by him for poverty, austerity, and harvesting coupled with rising interest on his loan amount eventually pushes him and his entire family to commit suicide. Farmer suicide in India is a situation arising after 1990 in which reports of suicides have been recorded by more than ten thousand farmers every year. Between1991 and 2007, 17306 farmers committed suicide. Indian agriculture is heavily dependent on the monsoon and the destruction of cash crops due to the failure of the monsoon has been considered to be the main cause of farmer suicides. Circumstances such as monsoon failure, drought, price rise, excessive debt burden, etc. start a cycle of problems. Farmers of various parts of India have committed suicide by getting trapped in a cycle of banks, money lenders, middlemen, etc. In order to understand the impact of globalization on Indian agriculture, to understand the current problem of farmer suicides, globalization, and farmer suicides in India have chosen this topic for my research paper.